PENGARUH KREDIBILITAS CELEBRITY ENDORSER, DAYA TARIK IKLAN, DAN BRAND AWARENESS TERHADAP BRAND ATTITUDE - Dityani, Alda; Kusumadewi, Ni Made Wulandari; Suryani, Alit (E-Jurnal Manajemen, 2014)
The development of the current technology is progressing very rapidly. Various products with high technology began to be mass produced and marketed throughout the world particularly in Indonesia, one of them in the field of telecommunications. Cell phones or mobile phones, are now becoming part of the needs and lifestyle of nearly all walks of life in Indonesia and has increased every year. A brand attitude arises from one's self through celebrity endorser credibility, attraction advertising, and brand awareness. The purpose of this study was to determine the effect of celebrity endorser credibility, attraction advertising, brand awareness and brand attitude towards mobile phone brands MITO. Based on the results of the analysis found that: celebrity endorser credibility, attraction advertising, and brand awareness have significant and positive effect on brand attitude MITO cell phone. Keyword : celebrity endorser, attraction advertising, brand awareness, dan brand attitude
Keywords: celebrity endorser, attraction advertising, brand awareness, dan brand attitude